GEOLOGY AND GEOCHEMICAL CHARACTERISTICS OF MESOZOIC GRANITOID ROCKS AND ASSOCIATED MINERALIZATION FROM THE WESTERN KALIMANTAN ISLAND, INDONESIA - , KYAW LINN ZAW ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The study area is located in the western part of Kalimantan, between the latitude 2Âº 15âS to 2Âº 15âN, and longitudes 108Âº 55â and 113Âº 10âE. The six administrative districts within the study area are administered respectively from the towns of Sanggau, Singkawang, Sambas, Pontianak, Ketapang and Nangapinoh. Kalimantan can be divided into several roughly E-W trending tectonic provinces. The northern portion of the island is dominated by the Cretaceous and Eocene to Miocene geological units. The Schwaner Batholith itself is a triangular exposure of Cretaceous granitic rocks which intrude into Paleozoic and Mesozoic volcanics, volcaniclastics, and marine sediments. The main purpose of this research work is to understand the geology and geochemical characteristics of granitoid rocks of the area and to establish the relation of its rocks with association of mineralization in the area. The analytical methods such as petrography, ore mineralogy, X-ray Fluorescence (XRF) and Inductively Coupled Plasma Mass Spectroscopy (ICP-MS) have been conducted for this research. The granites, granodiorites, tonalites, quartz monzonites, and quartz monzodiorites of the western Kalimantan area have calc-alkaline fractionation trends that are consistent with magmas formed at volcanic arc setting. Characteristics vary slightly between samples but generally have I-type signatures. Normalized trends and tectonic comparisons for REE suggest that the granitoid rocks from the area are the crystallization product of an initial partial melting of any combination of volcanic-arc environment and active continental margins. Mineralizations are mostly associated with Cretaceous granites bodies and some are related with younger Miocene intrusive rocks which are mostly occured along the marginal parts of granite plutons. It is also related with structural control that can be seen at the deposit scale. This mineralization displays both of the shallow level to deep level environments. Potential mineralizations have the highest copper grade of 26,500 ppm, zinc 369,000 ppm, lead 216,000 ppm, silver 1,580 ppm, cassiterite 31,200 ppm and manganese 10,100 ppm. Other base element nickel (Ni) and chromite (Cr) have low contents, in which the highest grade for nickel is only 20 ppm and chromite is merely 290 ppm.